Rare earth modified titanium-based alloy, preparation method thereof and metal implant

By adding 钪 elements to titanium alloy, SC2O3 oxides are formed to inhibit the transformation of the mimlinoma, develop a rare earth modified titanium alloy, solve the problem of high elasticity of traditional metal implants material and toxicity. The low elastic modulus and good biocompatibility of the alloy.

CN119372523APending Publication Date: 2025-01-28XIAMEN INST OF RARE EARTH MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411555845.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The elastic modulus of traditional medical metal implant materials is higher than that of human bones, resulting in stress shielding effects, hindering bone conduction, causing bone resorption and loosening, and contains elements that are toxic or sensitized to the human body.

Method used

Develop a rare earth modified titanium alloy, to form SC2O3 oxides by adding 钪 elements, inhibit the transformation of Matoelite, reduce the amount of elastic modulus, and obtain alloys through hot rolling, solid -soluble treatment, water quenching and cold rolling process.

Benefits of technology

The obtained rare earth modification titanium alloy has extremely low elastic modulus, good biocompatibility and mechanical properties. It is suitable for the preparation of human metal implants, reducing the risk of bone absorption and loosening.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372523A_ABST
    Figure CN119372523A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of titanium alloy materials, and particularly relates to a rare earth modified titanium-based alloy, a preparation method thereof and a metal implant. The rare earth modified titanium-based alloy provided by the invention comprises the following element components in percentage by mass: 24-28% of niobium, 2-6% of zirconium, 2-6% of tin, 0.001-2% of molybdenum, 0.001-2% of tantalum, 0.001-2% of scandium and the balance of titanium. Sc2O3 formed by Sc and scandium is added into the titanium-based alloy to inhibit the martensite transformation process, when the rare earth modified titanium-based alloy is induced by stress, beta-martensite phase transformation occurs originally, but due to the existence of scandium oxide, the transformation process is inhibited, and on the contrary, part of martensite can be reversed to return to the beta phase, so that the rare earth modified titanium-based alloy is subjected to stress induction. Therefore, hyperelasticity is obtained, and the elastic modulus is reduced; the rare earth modified titanium-based alloy has extremely low elastic modulus, good mechanical property and good biocompatibility, and is suitable for preparation of human body metal implants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium alloy materials, and in particular relates to a rare earth modified titanium-based alloy and a preparation method thereof, and a metal implant. Background Art

[0002] With the increasing trend of global aging and the rapid development of medical technology, the market for medical superelastic alloys is showing a sustained growth momentum. At present, in the field of medical implant materials, the elastic modulus of traditional medical metal materials such as medical stainless steel (210GPa), CoCrMo alloy (240GPa), and Ti6Al4V alloy (110GPa) is much higher than that of human bones (30GPa). This huge difference in elastic modulus will lead to a "stress shielding" effect, hindering stress conduction in the bone, causing bone absorption and loosening near the implant, which will cause bone loss over a long period of time and increase the risk of secondary surgery. At the same time, these traditional medical implant materials contain elements that are toxic or sensitizing to human tissues, such as Al, V, Ni, etc. These problems limit the application of metal implant materials. Therefore, it is necessary to design new non-toxic implant materials with elastic modulus closer to human bones to solve the problems existing in traditional metal implant materials. Summary of the invention

[0003] In view of this, the present invention provides a rare earth modified titanium-based alloy and a preparation method thereof, and a metal implant. The rare earth modified titanium-based alloy provided by the present invention has good biocompatibility and an extremely low elastic modulus, and is suitable for preparing human metal implants.

[0004] In order to solve the above technical problems, the present invention provides a rare earth modified titanium-based alloy, comprising the following element components in percentage by mass:

[0005]

[0006] Preferably, the following element components are included in percentage by mass:

[0007]

[0008] Preferably, the rare earth modified titanium-based alloy has an elastic modulus of 35 to 46 GPa, a tensile strength of 600 to 650 MPa, an elongation of 15 to 48%, and a superelasticity of 1.5%.

[0009] The present invention also provides a method for preparing the rare earth modified titanium-based alloy described in the above technical solution, comprising the following steps:

[0010] A niobium source, a zirconium source, a tin source, a molybdenum source, a tantalum source, a scandium source and a titanium source are mixed according to the element ratio, smelted and then cooled to obtain a titanium alloy ingot;

[0011] The titanium alloy ingot is sequentially subjected to hot rolling, solution treatment, water quenching and cold rolling to obtain the rare earth modified titanium-based alloy.

[0012] Preferably, the smelting is vacuum smelting, the temperature of the vacuum smelting is 3200-3500° C., the number of vacuum smelting is 3-4 times, and the time of each vacuum smelting is 10-15 minutes.

[0013] Preferably, the temperature after cooling is 20-35°C.

[0014] Preferably, the hot rolling temperature is 850-1050° C., and the hot rolling deformation in the thickness direction is 60-80%.

[0015] Preferably, the temperature of the solution treatment is 1000-1200° C., and the holding time of the solution treatment is 25-35 min.

[0016] Preferably, the cold rolling is performed 5 to 7 times, and the deformation amount of the cold rolling in the thickness direction is 20 to 35%.

[0017] The present invention also provides a metal implant, which is prepared from the rare earth modified titanium-based alloy described in the above technical solution or the rare earth modified titanium-based alloy prepared by the preparation method described in the above technical solution.

[0018] The present invention provides a rare earth modified titanium-based alloy, comprising the following element components in percentage by mass: 24-28% niobium, 2-6% zirconium, 2-6% tin, 0.001-2% molybdenum, 0.001-2% tantalum, 0.001-2% scandium and the balance titanium. Scandium is added to the titanium-based alloy, and the Sc2O3 oxide formed by Sc will inhibit the martensitic transformation process. When the rare earth modified titanium-based alloy is induced by stress, the β-martensitic phase transformation will occur, but the presence of scandium oxide hinders this transformation process, and instead allows a part of the martensite to reverse and transform back to the β phase, thereby obtaining superelasticity and reducing the elastic modulus. The rare earth modified titanium-based alloy provided by the present invention has both good mechanical properties and good biocompatibility, and is suitable for the preparation of human metal implants. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 XRD spectra of TNZSMT-Sc, TNZSMT-Sc-cold rolled, and TNZSMT;

[0020] Figure 2 XRD spectra of TNZSMT-La and TNZSMT-Y;

[0021] Figure 3DTA curves of TNZSMT-Sc, TNZSMT, TNZSMT-La and TNZSMT-Y;

[0022] Figure 4 The stress-strain curves of TNZSMT, TNZSMT-Sc, TNZSMT-La, TNZSMT-Y and TNZSMT-Sc-cold rolled;

[0023] Figure 5 Polarization curves of TNZSMT, TNZSMT-Sc, TNZSMT-La and TNZSMT-Y in Hank's simulated body fluid;

[0024] Figure 6 is the cyclic loading curve of TNZSMT-cold rolled;

[0025] Figure 7 This is the cyclic loading curve of TNZSMT-Sc-cold rolled;

[0026] Figure 8 TEM image of TNZSMT;

[0027] Fig. 9 TEM image of TNZSMT-Sc;

[0028] Fig.10 It is a bar graph comparing the effects of TNZSMT and TNZSMT-Sc on the activity of MG 63 osteoblasts;

[0029] Fig.11 This is a bar graph comparing the effects of TNZSMT and TNZSMT-Sc on the osteoblast differentiation ability of MG 63 cells. DETAILED DESCRIPTION

[0030] The present invention provides a rare earth modified titanium-based alloy, comprising the following element components in percentage by mass:

[0031]

[0032]

[0033] Calculated by mass percentage, the rare earth modified titanium-based alloy provided by the present invention includes 24-28% niobium, and may be 26-28%.

[0034] Calculated by mass percentage, the rare earth modified titanium-based alloy provided by the present invention includes 2-6% zirconium, which may be 2-4%.

[0035] Calculated by mass percentage, the rare earth modified titanium-based alloy provided by the present invention includes 2-6% tin, which may be 2-4%.

[0036] In terms of mass percentage, the rare earth modified titanium-based alloy provided by the present invention includes 0.001-2% molybdenum, which may be 1-2%.

[0037] Calculated by mass percentage, the rare earth modified titanium-based alloy provided by the present invention includes 0.001-2% tantalum, which may be 1-2%.

[0038] Calculated by mass percentage, the rare earth modified titanium-based alloy provided by the present invention includes 0.001-2% scandium, which may be 0.5-2%.

[0039] Calculated by mass percentage, the rare earth modified titanium-based alloy provided by the present invention also includes a balance of titanium.

[0040] In the present invention, the rare earth modified titanium-based alloy contains β phase and a small amount of α″ phase, and the α″ phase basically disappears after cold rolling; the elastic modulus of the rare earth modified titanium-based alloy can be 35-46GPa, the tensile strength can be 600-650MPa, the elongation can be 15-48%, and the superelasticity can be 1.5%.

[0041] In the present invention, niobium, zirconium, molybdenum and tantalum mainly play a role in stabilizing the β phase, and tin and scandium will affect the phase transformation of the alloy so that the alloy has a lower elastic modulus; all elements used in the alloy of the present invention are non-toxic and have good biocompatibility, and the scandium element also has a certain effect of promoting the proliferation and differentiation of osteoblasts.

[0042] The present invention also provides a method for preparing the rare earth modified titanium-based alloy described in the above technical solution, comprising the following steps:

[0043] A niobium source, a zirconium source, a tin source, a molybdenum source, a tantalum source, a scandium source and a titanium source are mixed according to the element ratio, smelted and then cooled to obtain a titanium alloy ingot;

[0044] The titanium alloy ingot is sequentially subjected to hot rolling, solution treatment, water quenching and cold rolling to obtain the rare earth modified titanium-based alloy.

[0045] The present invention mixes a niobium source, a zirconium source, a tin source, a molybdenum source, a tantalum source, a scandium source and a titanium source according to the element ratio, smelts them and then cools them to obtain a titanium alloy ingot. As a specific embodiment of the present invention, the niobium source can be metal Nb, the zirconium source can be metal Zr, the tin source can be a Ti-Sn master alloy, the molybdenum source can be metal Mo, the tantalum source can be metal Ta, the scandium source can be rare earth Sc, and the titanium source can be metal Ti; the purity of the metal Nb, metal Zr, metal Mo, metal Ta, rare earth Sc and metal Ti can be ≥99.99wt% respectively, and the Ti content in the Ti-Sn master alloy can be 20wt%.

[0046] As a specific embodiment of the present invention, the smelting is vacuum smelting, and the temperature of the vacuum smelting can be 3200-3500°C, specifically 3200°C, 3300°C, 3400°C or 3500°C; the number of vacuum smelting can be 3-4 times, and the time of each vacuum smelting can be 10-15min, specifically 10min, 12min, 14min or 15min; the vacuum smelting can be carried out in a protective atmosphere, and the present invention has no special limitation on the type of protective gas providing the protective atmosphere, and a protective gas familiar to those skilled in the art can be used, such as argon; the temperature after cooling can be 20-35°C; the vacuum smelting can be carried out in an integrated vacuum non-consumable smelting furnace, and cold water is continuously passed to the bottom of the integrated vacuum non-consumable smelting furnace to quickly cool the molten liquid.

[0047] The present invention has no special restrictions on the shape and size of the titanium alloy ingot, which is directly determined by the shape and size of the crucible used for vacuum melting.

[0048] After obtaining the titanium alloy ingot, the present invention sequentially performs hot rolling, solution treatment, water quenching and cold rolling on the titanium alloy ingot to obtain the rare earth modified titanium-based alloy. As a specific embodiment of the present invention, the hot rolling temperature can be 850-1050°C, specifically 850°C, 900°C, 950°C, 1000°C or 1050°C; the hot rolling holding time can be 28-32 minutes, specifically 30 minutes; the hot rolling deformation in the thickness direction can be 60-80%, specifically 60%, 65%, 70%, 75% or 80%.

[0049] As a specific embodiment of the present invention, the temperature of the solid solution treatment can be 1000-1200°C, specifically 1000°C, 1100°C or 1200°C; the holding time of the solid solution treatment can be 25-35min, specifically 25min, 30min or 35min. The present invention can make the alloy structure uniform, reduce the influence of residual stress, and stabilize the mechanical properties of the alloy through solid solution treatment.

[0050] As a specific embodiment of the present invention, the solution treatment may further include: sequentially water quenching and surface grinding the product after the solution treatment.

[0051] As a specific embodiment of the present invention, the cold rolling can be performed 5 to 7 times, specifically 5, 6 or 7 times; the cold rolling deformation in the thickness direction can be 20 to 35%. The present invention can reduce the elastic modulus of the alloy through cold rolling (increase dislocation, inhibit martensitic phase transformation, and provide deformation energy storage).

[0052] The present invention also provides a metal implant, which is prepared from the rare earth modified titanium-based alloy described in the above technical solution or the rare earth modified titanium-based alloy prepared by the preparation method described in the above technical solution. As a specific embodiment of the present invention, the metal implant can be a human bone implant.

[0053] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0054] Example 1

[0055] Metal Ti, metal Nb, metal Zr, metal Mo, metal Ta, rare earth Sc and Ti-Sn master alloy are mixed to obtain a mixed raw material; the purity of metal Ti, metal Nb, metal Zr, metal Mo, metal Ta and rare earth Sc is 99.99wt%, and the Ti content in the Ti-Sn master alloy is 20wt%;

[0056] In an argon protective atmosphere, the mixed raw materials were subjected to vacuum non-consumable arc melting for 3 times, wherein the melting temperature was 3500°C and the single melting time was 15 minutes; the molten liquid obtained after the melting was cooled to 30°C by cooling water to obtain a titanium alloy ingot;

[0057] The ingot was hot rolled at 900°C with a deformation of 77.8% in the thickness direction to obtain a hot-rolled plate with a thickness of 10 mm; the hot-rolled plate was kept at 1000°C for solution treatment for 30 minutes to obtain a solution plate (denoted as TNZSMT-Sc); the solution plate was water quenched, surface polished and cold rolled for multiple passes in sequence to obtain a rare earth modified titanium-based alloy with a thickness of 7 mm (denoted as TNZSMT-Sc-cold rolled), wherein the number of cold rolling passes was 6, with no intermediate annealing between adjacent cold rolling passes, and the deformation in the thickness direction was 30%; the composition of the obtained rare earth modified titanium-based alloy was as follows, in terms of mass percentage: 26% Nb, 4% Zr, 4% Sn, 1% Mo, 1% Ta, 0.5% Sc and the remainder Ti.

[0058] Comparative Example 1

[0059] A titanium-based alloy was prepared according to the method of Example 1, except that the rare earth Sc was omitted. The element composition of the prepared titanium-based alloy (denoted as TNZSMT-cold rolled) was: 26% Nb, 4% Zr, 4% Sn, 1% Mo, 1% Ta and the remainder Ti, in terms of mass percentage.

[0060] Comparative Example 2

[0061] A titanium-based alloy was prepared according to the method of Comparative Example 1, except that the steps of water quenching, surface grinding and multi-pass cold rolling after solid solution were omitted. The element composition of the prepared titanium-based alloy (denoted as TNZSMT) was, in terms of mass percentage, 26% Nb, 4% Zr, 4% Sn, 1% Mo, 1% Ta and the remainder Ti.

[0062] Comparative Example 3

[0063] A titanium-based alloy was prepared according to the method of Example 1, except that the rare earth Sc was replaced by rare earth La, and the steps of water quenching, surface grinding and multiple cold rolling after solid solution were omitted; the element composition of the prepared titanium-based alloy (denoted as TNZSMT-La) was, in terms of mass percentage, 26% Nb, 4% Zr, 4% Sn, 1% Mo, 1% Ta, 0.5% La and the remainder Ti.

[0064] Comparative Example 4

[0065] A titanium-based alloy was prepared according to the method of Comparative Example 1, except that the rare earth Sc was replaced by rare earth Y, and the steps of water quenching, surface grinding and multiple cold rolling after solid solution were omitted; the element composition of the prepared titanium-based alloy (denoted as TNZSMT-Y) was, in terms of mass percentage, 26% Nb, 4% Zr, 4% Sn, 1% Mo, 1% Ta, 0.5% Y and the remainder Ti.

[0066] The solid solution plate (TNZSMT-Sc) and rare earth modified titanium-based alloy (TNZSMT-Sc-cold rolled) prepared in Example 1 and the titanium-based alloy (TNZSMT) prepared in Comparative Example 2 were tested using an X-ray diffractometer (XRD, Rigaku D / Max 2500, Cu-Kα ray) to obtain XRD spectra. Figure 1 As shown. During the detection process, the acceleration voltage and current were 40kV and 250mA respectively, the scanning speed was 1° / min, and the scanning range was 30-80°. Then, the obtained X-ray diffraction pattern was analyzed using MDI Jade 6.0 software to characterize the phase composition of the alloy. Figure 1 It can be seen that the content of α″ phase in TNZSMT is higher, the content of α″ phase in TNZSMT-Sc is less, and the α″ martensite in TNZSMT-Sc-cold rolled almost disappears.

[0067] The titanium-based alloys prepared in Comparative Example 3 (TNZSMT-La) and Comparative Example 4 (TNZSMT-Y) were tested using an X-ray diffractometer (XRD, Rigaku D / Max 2500, Cu-Kα ray) to obtain XRD spectra. Figure 2 As shown. Combined Figure 1 and Figure 2 It can be seen that compared with the TNZSMT matrix, the martensite content in TNZSMT-La has not changed significantly; compared with the TNZSMT matrix, the martensite content in TNZSMT-Y has not changed significantly.

[0068] The phase transition temperature of TNZSMT-Sc in Example 1 and the titanium-based alloys prepared in Comparative Examples 2 to 4 in the solid solution state was measured by differential thermal analysis (DTA, Setaram Labsys Evo), and the DTA curve was obtained, as shown in FIG. Figure 3 As shown, the downward convex part of the curve corresponds to the martensitic phase transition temperature. The test was carried out in an Al2O3 crucible with a heating rate of 10K / min and Ar gas was used for protection throughout the process. Figure 3 The DTA results show that there is no obvious martensitic phase transformation peak in TNZSMT-Sc, there is an obvious martensitic phase transformation peak (130℃) in TNZSMT-La, and there is an obvious martensitic phase transformation peak (130℃) in TNZSMT-Y. The addition of 0.5wt% scandium makes the martensitic phase transformation peak of the alloy TNZSMT disappear at 130℃.

[0069] The results were obtained at room temperature using an Instron 3369 mechanical testing system ( Norwood, MA, USA) conducted tensile tests on TNZSMT, TNZSMT-Sc, TNZSMT-La, TNZSMT-Y and TNZSMT-Sc-cold rolled alloys, and the stress-strain curves were obtained as shown in Figure 4 As shown; the stretching rate is 3.33×10 -2 mm / s, the size of the tensile test sample is 30mm (length) × 4mm (width) × 1.5mm (thickness). A 10mm extensometer is used to obtain accurate strain. The yield strength (YieldStrength), tensile strength (Tensile Strength), and elastic modulus (E) of the alloy are obtained through the stress-strain curve. Three parallel samples are prepared for each alloy sample, and the final result is the average value. The results are listed in Table 1.

[0070] Table 1 Performance parameters of alloys prepared in Example 1 and Comparative Examples 2 to 4

[0071]

[0072] Combining Table 1 and Figure 4It can be seen that adding La and Y rare earth elements to the TNZSMT matrix not only does not reduce the elastic modulus of the alloy, but also has a very limited effect on improving the strength of the alloy. However, adding Sc elements not only significantly reduces the elastic modulus of the matrix, but also improves the strength of the alloy, especially after cold rolling, the elastic modulus of the alloy is reduced to 35GPa. Figure 4 It can be seen that after adding Sc, the TNZSMT alloy has stress-induced phenomenon, has a double yield point, and the ultimate strength is based on the tensile strength.

[0073] Electrochemical impedance spectroscopy (EIS) tests were performed on TNZSMT, TNZSMT-Sc, TNZSMT-La and TNZSMT-Y to obtain polarization curves as follows: Figure 5 As shown. The electrochemical tests were carried out at room temperature (about 24°C) using an IM6ex electrochemical workstation (ZAHNER, Germany) in Hanks solution (H6136, Sigma-Aldrich), using a traditional three-electrode system; the working electrode was the experimental alloy, the counter electrode was a platinum mesh, and the reference electrode was a saturated calomel electrode (SCE). The electrochemical potentials were all based on SCE. Before the electrochemical impedance spectroscopy (EIS) test, the open circuit potential (OCP) was measured for 2.5h to allow each test sample to reach a relatively stable state. The frequency range of the EIS test was 10KHz to 0.01kHz, and the low-amplitude AC signal was 10mV. Finally, after reaching a relatively stable state after the EIS test, a potential polarization test was performed. The potential was scanned from -1V (relative to OCP) to +2.50V, with a scan rate of 0.2mV / s. To ensure the repeatability of the data, each experiment was repeated at least three times. According to Figure 5 The self-corrosion potential and self-corrosion current were calculated and the results are listed in Table 2.

[0074] Table 2 Electrochemical performance parameters of the alloys prepared in Example 1 and Comparative Examples 2 to 4

[0075]

[0076] Cyclic loading tests were performed on TNZSMT-cold rolled and TNZSMT-Sc-cold rolled. The initial cycle was performed at a strain of 1.5%. Subsequent cycles were performed at the same stress level obtained in the initial cycle, with a stretching rate of 2 mm / min, and the cyclic loading curves were obtained, as shown in Figure 2. Figure 6 and 7 As shown, Figure 6 This is the cyclic loading curve of TNZSMT-cold rolled. Figure 7 is the cyclic loading curve of TNZSMT-Sc-cold rolled. Figure 6 and Figure 7 It can be seen that the elastic moduli of the first cycle of TNZSMT-coldrolled and TNZSMT-Sc-cold rolled alloys are 46 GPa and 35 GPa, respectively. TNZSMT-Sc-cold rolled exhibits complete superelastic behavior (1.5% recoverable strain), while TNZSMT-coldrolled has only 0.8% incomplete recovery strain.

[0077] The TNZSMT and TNZSMT-Sc were examined using a Tecnai G2 F20 transmission electron microscope (FEI Company, Hillsboro, Oregon, USA) at an operating voltage of 200 kV, and the TEM images were obtained, as shown in Figure 8 and Fig. 9 As shown. Through the microstructure morphology of the alloy, the crystal structure of the matrix phase and the precipitated phase is analyzed by selected area electron diffraction. Figure 8 and Fig. 9 It can be seen that TNZSMT has a large number of mutually perpendicular martensite distributions ( Figure 8 b is the α″ martensite selected area diffraction pattern), while more scandium oxides were found in TNZSMT-Sc ( Fig. 9 The black dot in b), the composition is as follows Fig. 9 As shown in d. Select Fig. 9 The corresponding bright field and dark field images of the α″ martensite selected area diffraction pattern in a are as follows Fig. 9 As shown in Figures b and c, it can be seen that these oxides cause the distortion of martensite. Therefore, the reason why scandium causes the martensitic phase transformation temperature to decrease is that scandium forms a sufficient amount of nano-scale oxides in the matrix. These oxides can easily cause martensite distortion and hinder the martensitic phase transformation. At the same time, because the elastic modulus of martensite is much higher than that of the matrix, the reduction in martensite content caused by the inhibitory effect of these oxides also leads to a further decrease in the elastic modulus.

[0078] The in vitro biocompatibility of TNZSMT and TNZSMT-Sc-coldrolled was characterized as follows, including their effects on the activity and differentiation ability of MG 63 osteoblasts. Fig.10As shown, the yellow column in the figure is the result of the blank control. Detection method: The proliferation ability of cells was measured by CCK 8 kit (Solarbio). After 1, 3, and 5 days of culture, the culture medium of MG 63 osteoblasts was aspirated and rinsed 3 times with PBS. 50 μL CCK-8 reagent and 450 μL regular culture medium were added to each well and placed in an incubator for 4 hours. Finally, the absorbance of the culture medium of each sample at 450 nm was detected on a microplate reader (Bio-Tek, Thermo Fisher Scientific, Waltham, Massachusetts, USA).

[0079] Depend on Fig.10 It can be seen that from the perspective of MG 63 osteoblast activity, starting from day 1 of culture, the activity of cells cultured on the TNZSMT-Sc surface was greater than that of the cell control group and the TNZSMT surface, and as the culture time increased, the difference in cell activity between the TNZSMT-Sc and TNZSMT surfaces became larger and larger, indicating that TNZSMT-Sc has better MG 63 osteoblast compatibility.

[0080] MG 63 osteoblasts were inoculated on the sample surface, cultured in cell culture medium for 3 days, and then replaced with bone induction medium. The culture medium was replaced every two days. After 3 days of differentiation induction, the cells were gently rinsed with PBS, fixed with 4% paraformaldehyde for 30 minutes, rinsed again with PBS, and then stained with BCIP / NBT colorimetric reagent. After staining, the cells were observed using a stereo microscope (OLYMPUS, SZX16, Japan) to qualitatively analyze the ALP activity of MG 63 osteoblasts on the surface of different samples. The specific value of ALP activity was tested using an alkaline phosphatase detection kit (Beyotime Biotechnology), and the absorbance wavelength was 570nm. According to the test results, a bar chart comparing the effects of TNZSMT and TNZSMT-Sc on the differentiation ability of MG 63 osteoblasts was drawn, as shown in the figure. Fig.11 As shown, the yellow columns in the figure are the results of the blank control.

[0081] from Fig.11 It can be seen that alkaline phosphatase activity ALP showed that the osteoblast differentiation ability of MG 63 on the surface of TNZSMT-Sc was higher than that of TNZSMT and cell control group, indicating that its ability to promote osteoblast differentiation was higher than that of TNZSMT.

[0082] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A rare earth modified titanium-based alloy, characterized in that: Includes the following elemental components in mass percentage:

2. The rare earth modified titanium-based alloy according to claim 1, characterized in that: Includes the following elemental components in mass percentage:

3. The rare earth modified titanium-based alloy according to claim 1, characterized in that: The rare earth modified titanium-based alloy has an elastic modulus of 35-46 GPa, a tensile strength of 600-650 MPa, an elongation of 15-48%, and a superelasticity of 1.5%.

4. The method for preparing the rare earth modified titanium-based alloy according to any one of claims 1 to 3, comprising the following steps: A niobium source, a zirconium source, a tin source, a molybdenum source, a tantalum source, a scandium source and a titanium source are mixed according to the element ratio, smelted and then cooled to obtain a titanium alloy ingot; The titanium alloy ingot is sequentially subjected to hot rolling, solution treatment, water quenching and cold rolling to obtain the rare earth modified titanium-based alloy.

5. The preparation method according to claim 4, characterized in that: The smelting is vacuum smelting, the temperature of the vacuum smelting is 3200-3500° C., the number of vacuum smelting is 3-4 times, and the time of each vacuum smelting is 10-15 minutes.

6. The preparation method according to claim 4 or 5, characterized in that: The temperature after cooling is 20-35°C.

7. The preparation method according to claim 4, characterized in that: The temperature of the hot rolling is 850-1050° C., and the deformation amount of the hot rolling in the thickness direction is 60-80%.

8. The preparation method according to claim 4, characterized in that: The temperature of the solution treatment is 1000-1200° C., and the holding time of the solution treatment is 25-35 minutes.

9. The preparation method according to claim 4, characterized in that: The number of cold rolling passes is 5 to 7 times, and the deformation amount of the cold rolling in the thickness direction is 20 to 35%.

10. A metal implant, characterized in that: The invention is prepared from the rare earth modified titanium-based alloy described in any one of claims 1 to 3 or the rare earth modified titanium-based alloy prepared by the preparation method described in any one of claims 4 to 9.